Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Masa Pandemi Covid-19 ( Studi Kasus PT. Karya Mitra Budisentosa Pandaan) - Rizky Amelia Husniyah; Jeni Susyanti; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of Work Discipline and Job Satisfaction on Employee Performance Study on employees of PT. Karya Mitra Budisentosa Pandaan.. The type of research used is quantitative research with questionnaire distribution method. The sample in this study were 85 respondents and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination The variables used in this study are performance variables (the dependent variable), while the independent variables are Work Discipline and Job Satisfaction on Employee performance. The results of this study conclude that the variable work discipline and job satisfaction have a partical effect on employee performance. Keywords: Employee Performance, Work Discipline and Job Satisfaction